EMPOWERMENT OF AA MICRO BUSINESS IN DEVELOPING DIVERSICATION OF CAKE PRODUCTS IN SURABAYA - Dr. H. Zakariya, MS., MM.; Drs. Ec. Kunto Inggit Gunawan, MM.; Drs. Ec. Mataji, MM. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
Since the enactment of the Asean Economic Community (AEC) at the end of 2015 should encourage all economic actors including SMEs and Micro Enterprises to improve themselves in order to improve the quality of production of both goods and services. If it is not done, then Indonesia is a